2007
DOI: 10.1021/jp072354j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Iron Oxide Acid−Base Properties on the Chemisorption of Model Epoxy Compounds Studied by XPS

Abstract: In this work, the influence of the iron oxide acid−base properties on the adsorption of model epoxy compounds was examined. To study this, iron oxide layers with a different surface hydroxyl fractions were prepared in controllable and reproducible conditions. The surfaces were characterized by X-ray photoelectron spectroscopy (XPS). An expression for the hydroxyl fraction of the oxide films was deduced, starting from the measured XPS intensities. Two model epoxy compounds characteristic of an epoxy/amide syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
120
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 112 publications
(129 citation statements)
references
References 48 publications
5
120
1
Order By: Relevance
“…2. [4] Although the variation of − coat across the different oxide films is relatively small compared with the potential shifts observed after adsorption of epoxy-amide model molecules (e.g. due to lower density of groups interacting with oxide surface), − coat is the highest for the hydroxyl-rich surfaces and the lowest for the hydroxyl-poor surfaces.…”
Section: Gasmentioning
confidence: 99%
See 2 more Smart Citations
“…2. [4] Although the variation of − coat across the different oxide films is relatively small compared with the potential shifts observed after adsorption of epoxy-amide model molecules (e.g. due to lower density of groups interacting with oxide surface), − coat is the highest for the hydroxyl-rich surfaces and the lowest for the hydroxyl-poor surfaces.…”
Section: Gasmentioning
confidence: 99%
“…Recently, Wielant et al [4,5] made a detailed simulation of the adhesion of an epoxy-amide coating by adsorbing two different model compounds (N,N -dimethylsuccinamide and Nmethyldiethylamine) on differently treated steel surfaces. It was observed that the hydroxyl density at the oxide surface could be assumed as the most crucial surface property toward adsorption of these molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, most research efforts focused on controlling the film morphology, such as the pore diameter, oxide layer and barrier layer thickness. However, numerous studies [3][4][5][6][7] provide evidence for the significance of the oxide chemistry in the interfacial bonding with an organic coating.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Since most analysis techniques are not able to probe interactions at the buried interface, adhesion is often modelled by the adsorption of functional molecules representing the resin on the metal surfaces. [4,10,11] This type of measurements offers valuable information about bonding mechanisms on a molecular level. Additionally, the adsorption of various molecules on different surface oxides provides an indication of the nature of the oxide, such as its activity and its acid-base properties.…”
Section: Introductionmentioning
confidence: 99%